THE INFLUENCE OF YOGA ATTRACTIONS AND SERVICE EXCELLENCE ON CUSTOMER LOYALTY AT PRAMA SANUR BEACH HOTEL, DENPASAR TIMUR - Ni Ketut Erawati; I Nyoman Subagia; I Ketut Wardana Yasa (Ride: Journal of Cultural Tourism and Religious Studies, 2024)
Attractions and service excellence provide significant influence​ to loyal customers , because existing facilities​ hotel and quality services provided​ proven capable interesting visitor For come return . The purpose of study This is For know exists influence yoga attraction to customer loyalty , influence service excellence to Customer loyalty and existence influence yoga attractions and service excellence to loyal customers . Types of research This is analysis descriptive quantitative . Respondent from study This is staying guests​ as loyal customer​ for 2 years lastly at the Prama Sanur Beach Hotel, East Denpasar with amount population 1,155 people. The sampling technique used in study This is purposive sampling so sample totaling 92 people. Data collection techniques were carried out through questionnaires and interviews . Data analysis method used is analysis multiple linear regression . Research result This obtain equality regression : Y= 6.335 + 0.149 + 0.746 With table t value 1.662, table F value 3.09, and level significance 5% (0.05). Based on test results​ Partial prove that : 1) variable yoga attractions have t- count > t table 2.626 with mark significance 0.10 < 0.05 and value its influence amounting to 31.0% 2) variable service excellence has t- count 10.665 > t table 1.662 with mark significance 0.00 < 0.05 and value its influence by 54.2%. This result showing that yoga attractions and service excellence influential to loyal customers . 3) Overall test results simutan has an F-count of 59.941 > F table with mark significance 0.000 < 0.05. Whereas mark Adjusted R2 0.574 explain that amounting to 56.4% of yoga attractions and service excellence own contribution For influence loyal customers . As for the rest 43.6% influenced factor others who don't explained in the research model This like Power pull , factor social , and factors nature .